Making Dispute Resolution More Effective - MAP Peer Review Report, Singapore (Stage 2) (OECD Publishing, 2020)
Under Action 14, countries have committed to implement a minimum standard to strengthen the effectiveness and efficiency of the mutual agreement procedure (MAP). The MAP is included in Article 25 of the OECD Model Tax Convention and commits countries to endeavour to resolve disputes related to the interpretation and application of tax treaties. The Action 14 Minimum Standard has been translated into specific terms of reference and a methodology for the peer review and monitoring process. The minimum standard is complemented by a set of best practices. The peer review process is conducted in two stages. Stage 1 assesses countries against the terms of reference of the minimum standard according to an agreed schedule of review. Stage 2 focuses on monitoring the follow-up of any recommendations resulting from jurisdictions' Stage 1 peer review report. This report reflects the outcome of the Stage 2 peer monitoring of the implementation of the Action 14 Minimum Standard by Singapore.
10.1787/3d152880-en
Keywords: Amtsdruckschrift; Graue Literatur; Konfliktregelung; Internationales Steuerrecht; Steuervermeidung; Gewinnverlagerung; Steuererhebungsverfahren; OECD-Staaten; G20-Staaten; Singapur; Taxation; Singapore